Confidence in and valuing of psychological findings among preservice teachers - Seifried, Eva; Menz, Cordelia; Spinath, Birgit (Teaching of psychology, 2022)
BackgroundTeachers? perception of psychology is of importance because they get in contact with psychology as a scientific discipline and should apply (educational) psychological findings. This requires a generally positive attitude toward corresponding findings, which should be fostered during teacher education.ObjectiveThe goal of this study was to examine preservice teachers? perception of findings from psychology in general and educational psychology in particular, thereby differentiating between confidence in and valuing of the same.MethodTwo subsamples of n = 937 German preservice teachers and n = 310 psychology majors participated in an online survey.ResultsCompared with natural science disciplines or another ?harder? psychological subdiscipline, preservice teachers perceived psychology as less scientific, and judged findings from psychology and educational psychology to be less credible but more valuable. While both confidence in and valuing of findings from psychology were higher among psychology majors than among preservice teachers, the opposite was true for educational psychology. However, all differences were rather small.ConclusionWe conclude that preservice teachers? perception of (educational) psychology is not alarmingly poor.Teaching ImplicationsThe high valuing of scientific findings from (educational) psychology could be used to also foster a broader reliance on scientific findings (examples are discussed).
Gesehen am 06.02.2022